Investigating EFL Students' Politeness Strategies in Pedagogical WhatsApp Text Conversation - Rowiyah, Siti; Humaira, Nabila; Nurfitriana, Latifah (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The use of social media in human life recently is such normal direct interaction including in English language teaching. Politeness strategies are essential in social communication to keep convenient connections. This study aims to examine how politeness strategies are used in increasingly complex situations, combining social media and the pedagogical context of multiple members’ character, specifically in an EFL class WhatsApp group, and note any effects on students’ language acquisition. This research employs a qualitative methodology with a precisely descriptive case study procedure. The data in this study consists of the last two months’ WhatsApp group chats centered on English learning, specifically examining the usage of politeness methods as well as the results of a focused group discussion (FGD) involving six English as a Foreign Language (EFL) randomly selected students who are members of the WhatsApp group. The result shows that students use positive and negative politeness strategies during the WhatsApp conversation. It enhances their English language learning motivation, critical thinking skills, vocabulary enrichment, writing improvement, and raising awareness of English grammar skills. Therefore, applying politeness strategies in WhatsApp instructional conversations is advantageous in preventing the failure of effective communication during the learning process.